Model of church as cyberchurch –neighborhood of “other/s” - Jacoba, Rico Casta (Animo Repository, 2022)
The internet revolution is said to be comparable to the Industrial Revolution in terms of impact on society. In this new context, how can we re-conceive the church? This dissertation offers the model of Cyberchurch Neighborhood of Other/s as one way of re-imagining the church and its mission in the cyber-context. As theoretical framework, this study presupposes that the online church, if ever linked to the local church, complements and enhances the offline church and vice-versa. This dissertation examines the problem: How can one describe a model of church as cyberchurch neighborhood of other/s? Toward this end, it first mapped cyberchurches based on their context of emergence and presence/absence of link to the local church. It then analyzed the discourses on neighbor, other and the Filipino concept of kapwa, and used inclusivist interpretations that are sensitive to the challenge of the “other” as lens to re-read the parable of the Good Samaritan. Employing the framework of Avery Dulles for analyzing church models, the study synthesized and expounded on the basic characteristics, strengths, and limitations of the model of cyberchurch neighborhood of other/s. The cyberchurch neighborhood of other/s has a strong foundation in Scripture, particularly in Matthew 18:20 “[F]or where two or three gathers in my name, there am I with them” that allows those who are unable to meet in-person for various reasons to gather in communities in cyberspace. The parable of the good Samaritan in turn can be re-read as an exhortation to be a good neighbor in the cyber-highway. The cyberchurch members are united by their fellowship as neighbors on the cyberhighway of life. A major block in the development of cyberchurches neighborhood of others is the digital divide that may exclude those who are not wired from full participation in the church.